When people are away the cats will play: African leopards alter visitation patterns at a safari guest lodge in association with the COVID-19 quietus on Loisaba Conservancy, Kenya - Nicholas W. Pilfold; Laiyon Lenguya; Ambrose Letoluai; Hannah Campbell; Megan A. Owen (Global Ecology and Conservation)
The COVID-19 pandemic significantly reduced human activity within protected areas during periods of government lockdowns, providing a natural experiment to study animal response to reduced human activity. At Loisaba Conservancy, Kenya, safari lodge operations were closed for more than a year during the COVID-19 pandemic. We recorded visitation of African leopards (Panthera pardus pardus) on a trail camera placed within a safari camp from March 1, 2018 – July 31, 2023, to assess the behavioral response of leopards to the cessation and resumption of human activity. Leopards were detected more frequently at the lodge during the COVID-19 quietus than either before or after, expanded their seasonal use to include more frequent visitation in the wet season, and spent more of their activity budget engaged in territorial marking. Our results suggest that African leopards have a relaxed avoidance of human activity in protected areas and will opportunistically occupy modified landscapes made available when humans are absent.